2024
DOI: 10.1002/adfm.202315563
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Janus Metal Atomic‐Site Catalysts for Efficient Polysulfide Conversion and Alkali Metal Deposition: Advances and Prospects

Guangfu Dai,
Shouzhe Li,
Menglin Shi
et al.

Abstract: Although metal–sulfur batteries (M–S batteries, M = Li, Na, K) are promising next‐generation energy‐storage devices because of ultrahigh theoretical energy density, low cost, and environmentally friendliness, their practical applications are significantly hindered by the shuttle effect of polysulfides and growth of alkali metal dendrites. These issues can be mitigated by using Janus metal atomic‐site catalysts, which possess the maximum atom utilization efficiency (≈100%), adjustable electronic structures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 261 publications
0
2
0
Order By: Relevance
“…Regarding P-doped materials, the characterization results disclose the existence of highly dispersed Fe species (Figure b–e) with Fe–N and Fe–P bonds, along with small Fe 2 P nanoclusters (Figures and S4–S7). As the P element has a larger atomic radius and higher electron-donating ability, P-doping can effectively modulate the coordination environment of Fe atoms, endowing Fe–P active sites with high activity. , Previous studies have consistently reported the effectiveness of Fe–P sites, specifically Fe 2 P and FeN 3 P 1 , in peroxymonosulfate activation and electrocatalytic oxygen reduction. , Therefore, it can be speculated that the active sites present in P-doped materials are FeN x P y and Fe 2 P. ,,, With an increase in Fe loading, the intensity of the Fe 2 P species in Fe 2 P­( x )@P­(1.0)­NC-950 increases and the reduction rate is enhanced (Figures a, a,b, and S4). The regeneration experiments revealed that the deactivated material could restore its original activity after the phosphating treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding P-doped materials, the characterization results disclose the existence of highly dispersed Fe species (Figure b–e) with Fe–N and Fe–P bonds, along with small Fe 2 P nanoclusters (Figures and S4–S7). As the P element has a larger atomic radius and higher electron-donating ability, P-doping can effectively modulate the coordination environment of Fe atoms, endowing Fe–P active sites with high activity. , Previous studies have consistently reported the effectiveness of Fe–P sites, specifically Fe 2 P and FeN 3 P 1 , in peroxymonosulfate activation and electrocatalytic oxygen reduction. , Therefore, it can be speculated that the active sites present in P-doped materials are FeN x P y and Fe 2 P. ,,, With an increase in Fe loading, the intensity of the Fe 2 P species in Fe 2 P­( x )@P­(1.0)­NC-950 increases and the reduction rate is enhanced (Figures a, a,b, and S4). The regeneration experiments revealed that the deactivated material could restore its original activity after the phosphating treatment.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Previous studies have consistently reported the effectiveness of Fe−P sites, specifically Fe 2 P and FeN 3 P 1 , in peroxymonosulfate activation and electrocatalytic oxygen reduction. 28,63 Therefore, it can be speculated that the active sites present in P-doped materials are FeN x P y and Fe 2 P. 27,63,65,66 With an increase in Fe loading, the intensity of the Fe 2 P species in Fe 2 P(x)@P(1.0)NC-950 increases and the reduction rate is enhanced (Figures 2a, 3a,b, and S4). The regeneration experiments revealed that the deactivated material could restore its original activity after the phosphating treatment.…”
Section: Bromate Reduction Mechanismmentioning
confidence: 99%